2013
DOI: 10.1007/s10578-013-0360-3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Development and Social-Emotional Functioning in Young Foster Children: A Follow-up Study from 2 to 3 Years of Age

Abstract: Foster children (FC) are at risk of delayed development relative to their peers due to early caregiver disruptions and adverse experiences prior to placement. Descriptive analyses and linear mixed effects (LME models) were used to analyse the cognitive development and social-emotional functioning of 60 FC and 42 comparison children (CC) at 2 (T1) and 3 years (T2). Changes in group differences between T1 and T2 were examined, and significant group differences occurred on all cognitive scales, with the FC obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 47 publications
0
27
1
Order By: Relevance
“…However, the adoptive and foster parents in the present study were stable and permanent, were specially selected and trained to care for at-risk children and had a relatively higher socioeconomic status than what is common in Norway [ 34 , 78 ]. A study of foster parents in Norway also found that although foster children may have more cognitive deficits than those in a comparison group, there were no significant differences in their attachment style or in the foster parents’ ability to care for the children [ 79 , 80 ]. Thus, there are indications that most of the children who were placed with foster and adoptive parents were raised in normal, stable, caring family environments.…”
Section: Discussionmentioning
confidence: 99%
“…However, the adoptive and foster parents in the present study were stable and permanent, were specially selected and trained to care for at-risk children and had a relatively higher socioeconomic status than what is common in Norway [ 34 , 78 ]. A study of foster parents in Norway also found that although foster children may have more cognitive deficits than those in a comparison group, there were no significant differences in their attachment style or in the foster parents’ ability to care for the children [ 79 , 80 ]. Thus, there are indications that most of the children who were placed with foster and adoptive parents were raised in normal, stable, caring family environments.…”
Section: Discussionmentioning
confidence: 99%
“…The child–parent dyads in the present study were part of a larger follow‐up study comprising a group of foster children and a group of comparison children. More details about sample characteristics were published earlier (Jacobsen, Moe, Ivarsson, Wentzel‐Larsen, & Smith, ). This study was approved by the National Committees for Research Ethics and the Norwegian Social Science Data Services.…”
Section: Methodsmentioning
confidence: 99%
“…The fourth study measured 12-month changes in socio-emotional difficulties and competence among 56 Norwegian 2-year-olds in foster care (Jacobsen, Moe, Ivarsson, Wentzel-Larsen, & Smith, 2013), using the Infant-Toddler Social and Emotional Assessment (ITSEA). While baseline mean social-emotional difficulties T scores were unexpectedly low for children in care, so too were T scores for a Norwegian comparison group, suggesting the T score distributions (based on U.S. norms) are not valid for Norwegian toddlers.…”
Section: Reviewmentioning
confidence: 99%
“…Two of the studies measured changes in very young (i.e., 2- to 4-year-olds) children’s socio-emotional development over short periods. The first study measured small to moderate mean deterioration in internalizing ( d = .17) and externalizing ( d = .40) difficulties (but improved competence, d = .18) over 12 months among 2-year-olds in care (Jacobsen et al, 2013). The second measured a moderate mean improvement ( d = .45) over 18–24 months following entry into care (Stahmer et al, 2009).…”
Section: Reviewmentioning
confidence: 99%